Use of sedative-hypnotics and the risk of Alzheimer’s dementia: A retrospective cohort study - Lee, Joonki; Jung, Sun Jae; Choi, Jae-won; Shin, Aesun; Lee, Yu Jin (PloS one, 2018)
There has been a growing interest in the relationship between sedative-hypnotics use and the risk of Alzheimer's dementia (AD) risk. This study aimed to evaluate the risk of AD associated with the use of sedative-hypnotics. A retrospective cohort study was conducted with randomly selected 5% samples from ≥50 years old beneficiaries of National Health Insurance Service (NHIS) of Korea from January 2002 to December 2015. The exposure to sedative-hypnotics was defined when prescribed over 30 defined daily dose (DDD) after January 2004 and it was categorized by prescribed dosage, types and half-lives of benzodiazepines. Time-dependent Cox regression model with a lag period of 5-years was used to evaluate the association between use of sedative-hypnotics and the risk of subsequent AD. Sensitivity analysis was performed for restricting sedative-hypnotics only when prescribed with insomnia. A total of 268,170 subjects were identified and subjects exposed to sedative-hypnotics showed a higher risk of AD (HR: 1.79; 95% CI: 1.72-1.86) than those who were not. There was an increased risk of AD among subjects exposed to benzodiazepines or zolpidem (HR: 1.75; 95% CI: 1.67-1.82) and antidepressants or low-dose antipsychotics (HR: 1.63; 95% CI: 1.42-1.87). The risk of AD was increased regardless of dose of sedative-hypnotics and half-life among benzodiazepines, especially in exposure to more than 360 DDD of sedative-hypnotics (HR: 1.78; 95% CI: 1.60-1.99) and the long-acting benzodiazepine (HR:1.77; 95% CI: 1.65-1.89).